Harnessing Information and Communication Technologies (ICTs) to Address Urban Poverty : Emerging Open Policy Lessons for the Open Knowledge Economy - Wambogo Omole, Duncan (Taylor and Francis, 2013)
Urban poverty is a complex socio-economic problem. The expected doubling of the urban population relative to rural areas by 2050 without a corresponding economic and infrastructure growth will worsen the problem, especially in emerging economies. Poor urban residents face rising unemployment and underemployment, constrained access to financial services, market exploitation, poor housing, crime, unsatisfactory health services and scant education opportunities. Several players have attempted to address these problems through information and communication technologies. This paper isolated a few of these to determine critical success factors on the economic empowerment front.